COMFORT, AS AN ASPECT OF LIFE CYCLE ANALYSIS (LCA) TOWARD SUSTAINABLE BUILDINGS - Naumovski Mihail; Lazarevska Marijana; Dimkovski Darko (Faculty of Civil Engineering, 2022)
Life Cycle Assessment (LCA) is a standardized, science-based methodology that has been developed to evaluate the environmental impact of buildings, with respect to their processes, their materials and use (energy) throughout the whole life cycle of a building. LCA takes into consideration all the steps that lead from raw material through manufacture, distribution and usage to final disposal. LCA in construction tends to evaluate the environmental impacts throughout the entire life cycle of the building, including upstream and downstream processes associated with the production and disposal. LCA is one of the most promising techniques for an ecological design of buildings. However, in order to appeal to the benefits of LCA, it is important to know how to use LCA properly. In this paper, the use of LCA in the construction sector has been critically analyzed. The main aspects of LCA have been applied for a case study of a building in Copenhagen, Denmark.
Keywords: LCA analysis comfort LCA design sustainable building health life-being